PELATIHAN SOFT SKILL DALAM KAJIAN BADAN USAHA MILIK NAGARI (BUMNAG), UMKM TERHADAP PENGELOLA, PELAKU DAN PERANGKAT NAGARI, DEWAN PERWAKILAN MASYARAKAT DESA DAN KADER DI SAWAH LAWEH KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Yulihardi, Yulihardi; Malik, David; Amrullah, Amrullah (Komunitas Manajemen Kompetitif, 2024)
The purpose of this activity is to enhance the creativity and innovation of BUMNag (Village-Owned Enterprises) managers, MSME (Micro, Small, and Medium Enterprise) actors, and local community members by exploring their current intrapersonal skills, providing them with future challenges to overcome, and expanding their awareness of the role of networking (interpersonal skills) in today's technology era. The impact of this activity is that participants receive education aimed at behavioral change among BUMNag managers, MSME actors, and Nagari (village) officials to foster personal development (intrapersonal) and improve interpersonal skills for more effective interaction. This, in turn, is expected to support the development of BUMNag and MSMEs and enable Nagari officials to synchronize with community elements. The team conducted this activity through face-to-face meetings. The organizing team hopes that, as a result of the training, participants will show an increased interest in improving their soft skills to run their businesses more effectively.